Infrared-based metabolomics for discrimination of Andrographis paniculata (Burm. f.) Wall. ex nees accessions harvested at different ages and times - Yusof, Nur Athifah (2015)
Andrographis paniculata is a herbal medicine for inflammation treatment over decades. The plant active metabolites such as andrographolide and neoandrographolide are mostly reported to have a wide range of medicinal properties. However, these two metabolites and also other metabolites could be affected by many factors. Harvesting age and time are among the factors which could influence the content of the compounds and efficacy of plant bioactivity. Hence, the purposes of this study were to identify the variation of major metabolites between three selected accessions which harvested at different harvesting age and time, and correlated to their nitric oxide (NO) inhibitory activity. Metabolomics was utilized in detecting the differences in the metabolite profiles of these three accessions A. paniculata, 11265 (Perak, H), 11341 (Kelantan, P) and 11248 (Negeri Sembilan, T); which leaves were harvested at different ages and times. The discrimination of different harvesting ages and times were established by orthogonal partial least square-discriminant analysis (OPLS-DA) and characterized by Fourier Transform Infrared (FTIR) spectroscopy. Meanwhile, the harvesting age with the highest concentration of the major compounds particularly, andrographolide (A), and neoandrographolide (N) were further discriminated in order to compare between harvesting time of morning and evening. The partial least square (PLS) was applied to correlate the nitric oxide (NO) inhibitory and FTIR of the leaves harvested at different ages and times.The OPLS-DA results revealed that morning harvested A. paniculata leaves at 120 days after transplanting (DAT) for P and T accessions, and 150 DAT for H accession contained the highest concentrations of the major compounds. These findings were further correlated to NO inhibitory activity in order to identify either these major compounds have influenced on this bioactivity. The methanol crude extracts of A. paniculata accessions showed the IC50 values ranged between 10.61±0.97 to 49.60±4.02 μg/mL for these three accessions. Some of the values are comparable to that of curcumin (IC50, 14.69 μg/mL). The most potent samples in NO inhibition activity were represented by morning of 180 DAT for T and H accessions, and evening of 180 DAT for P accession. This study provides a standard procedure to harvest the A. paniculata leaves with highest potential of NO inhibitory activity. This spectroscopic-statistic approach could be useful as a quick guide for time and age of A. paniculata leaves should be harvested with targeted major compounds and highest potential for NO inhibitory activity.